Implementation of Agricultural Land Protection Policy in Barru Regency: A Systematic Literature Review (SLR) - ⁠Resky Nur Fadhilah; Syamsiah (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal